'Please, see me'; Informal and professional support of students with relatives with addiction problems: a three-year longitudinal qualitative study - Dorine M. van Namen; Sander R. Hilberink; Hein de Vries; Gera E. Nagelhout; AnneLoes van Staa (BMC, 2024)
Abstract Background and aim Addiction problems also affect the lives of family members. This study aims to examine: (1) young adult family members' experiences with informal and professional support in coping with the impact of relatives' addiction problems and (2) how these experiences evolve over time. Method A three-year longitudinal qualitative study. Four rounds of in-depth, semi-structured individual interviews were conducted. Thirty students aged 18-30 years, participated in the study at baseline. 93% participated in at least two interviews, and 80% participated three or four times. The Stress-Strain-Information-Coping-Support model was used, and Directed Content Analysis was applied. Findings Five major themes were extracted from the data: (1) Informal support; (2) Educational support; (3) Healthcare support; (4) Resilience factors; and (5) Developments over time. Informal and educational support were more often described as effective than healthcare support, although the number of participants who sought healthcare support increased over time. Effective elements of support included being able to discuss their experiences with people listening without judgment or unsolicited advice and having long-term relationships of trust with people from the social environment and professionals. Participants were mainly treated with Cognitive Behavioral Therapy (CBT) and Eye Movement Desensitization and Reprocessing (EMDR). Learning how to distinguish between accurate and inaccurate thoughts, especially about themselves, was considered effective. Body-oriented therapy was remarkably absent. Finding effective healthcare support was often a long and winding road through various therapies and therapists. Participants were not attracted to peer group interventions but needed advice on how to deal with their relatives. They also needed recognition by their relatives for harm done. This recognition was seldom given. Conclusions It is recommended to train educational and healthcare professionals to recognize the support needs of young people with relatives with addiction problems, to help them cope, or to refer them adequately. We also suggest broadening the scope of professional support offered to AFMs, including body-oriented and cultural interventions.